Comparison of the effects of peer- versus self-editing on linguistic accuracy of Iranian EFL students - Abadikhah, Shirin; Yasami, Fariba (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The present study aims at investigating the relative effects of peer versus self-editing on EFL students’ linguistic accuracy in writing composition... Forty-five Iranian EFL students were divided into two experimental groups (n=30) and one control group (n=15). The experimental groups received four treatment sessions, in which they were required to write two compositions and revise them. The first experimental group (editors) provided peerediting without receiving any feedback from their peers or teacher, and the second experimental group (receivers) received peer-editing from the editors. Both groups received training on how to edit and revise their compositions based on coded feedback. In the next session, the receivers were asked to revise their papers based on the symbols and write a second draft. In addition, the editors were required to self-edit their own drafts and compose a second draft. In order to determine the effectiveness of the treatments in their writing accuracy, preand post-tests were administered to all groups including the control group. The analysis of data indicated that both editors and receivers made significant improvements from pre-test to post-test compared to the control group. Considering the accuracy of linguistic features, it was found that out of 10 linguistic features targeted in this study, capitalisation, spelling, verb tense, and wrong word improved significantly for both groups.